KONTRIBUSI PAJAK REKLAME DALAM MENUNJANG PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN GORONTALO - Trisusanti Lamangida; Nindy Anggriyani Aday (Universitas Muhammadiyah Gorontalo, 2020)
In general, tax is one of the sources of state revenue whose purpose is to finance development. Advertisement Tax is a type of tax determined by the region as a component of regional tax revenue. This researchh aims to determine how the advertisement tax contribution in supporting local tax revenue. This is a qualitative approach using time series data and interviews. The results showed that the contribution of the billboard tax in Gorontalo Regency every year in the last 5 years (2015-2019) continued to decline as seen from the achievement of realization. However, it is still able to contribute in supporting the Regional Taxes of Gorontalo Regency each year on average of 3.42 percent of Regional Tax revenue.